2010
DOI: 10.1353/dem.0.0086
|View full text |Cite
|
Sign up to set email alerts
|

Last hired, first fired? black-white unemployment and the business cycle

Abstract: Past studies have tested the claim that blacks are the last hired during periods of economic growth and the first fired in recessions by examining the movement of relative unemployment rates over the business cycle. Any conclusion drawn from this type of analysis must be viewed as tentative because the cyclical movements in the underlying transitions into and out of unemployment are not examined. Using Current Population Survey data matched across adjacent months from 1989 to 2004, this paper provides the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
73
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(83 citation statements)
references
References 25 publications
8
73
0
2
Order By: Relevance
“…Counties with large shares of Hispanic and non-Hispanic black populations experienced relatively large recession-related increases in unemployment. This result is not consistent with the human capital perspective, and provides suggestive evidence that minority workers face disadvantages in the labor market irrespective of their educational attainment (Couch and Fairlie 2010). This also suggests that the economic structure of these places may be different than counties with large shares of non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Counties with large shares of Hispanic and non-Hispanic black populations experienced relatively large recession-related increases in unemployment. This result is not consistent with the human capital perspective, and provides suggestive evidence that minority workers face disadvantages in the labor market irrespective of their educational attainment (Couch and Fairlie 2010). This also suggests that the economic structure of these places may be different than counties with large shares of non-Hispanic whites.…”
Section: Discussionmentioning
confidence: 67%
“…For example, race- and gender-based discrimination may increase the likelihood of job loss among certain demographic groups, particularly during periods of poor macroeconomic conditions (Couch and Fairlie 2010). Declines in unionization and shifts in the structure of production (among other changes) have also increased the share of the labor force employed in precious jobs and at risk of experiencing poor labor market outcomes (Brady, Baker, and Finnigan 2013; Kalleberg 2011; Lobao 2014; Lobao and Hooks 2003).…”
Section: Work Labor Markets and The Great Recessionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the severity and frequency of financial shocks may be greater among black and Latino households rendering each dollar of liquid assets less valuable in mitigating risk for hardship. For example, the median duration of an unemployment spell in 2017 was nearly 4 weeks longer among black compared to white individuals (United States Department of Labor 2018) while job separation incidence is higher among black and Latino compared to white employees (Couch and Fairlie 2010;Couch et al 2018). Similarly, though rates of uninsurance have recently fallen dramatically following passage of the Affordable Care Act, the uninsurance rate among black and Latino individuals is 4 and 9 percentage points higher compared to white individuals (Artiga et al 2018).…”
Section: Differences In Financial Stability By Race and Ethnicitymentioning
confidence: 99%
“…In these organizations, the majority of skilled labor might still consist of nondesignated positions; in stark contrast to the unskilled labor market which historically consists of mostly designated employees (Webster, 1983). If companies follow a last in first out (LIFO) policy in their retrenchment practices this could also increase job insecurity levels of designated employees; research has also shown that when the business cycle weakens this is usually the case, even when there is no compelling evidence that black people were the last to be hired (Couch & Fairlie, 2010). As training and development is considered to be crucial for the effective implementation of EE/AA policies (Jain, Horwitz, & Wilkin, 2012), and when a situation exists in which these employees suffer a lack of development (Oosthuizen & Naidoo, 2010), these employees may experience more job security and seek to move to another working environment.…”
Section: Job Insecuritymentioning
confidence: 99%